2016
DOI: 10.1016/j.brs.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Inhibition Assessed with Paired-Pulse Transcranial Magnetic Stimulation is Modulated during Shortening and Lengthening Contractions in Young and Old Adults

Abstract: In all cases accepted manuscripts should: link to the formal publication via its DOI  bear a CC-BY-NC-ND license -this is easy to do, click here to find out how  if aggregated with other manuscripts, for example in a repository or other site, be shared in alignment with our hosting policy  not be added to or enhanced in any way to appear more like, or to substitute for, the published journal article Embargo 1935-861X Brain Stimulation 129 May 2017 Age-and movement-related changes in intracortical inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
5
13
0
Order By: Relevance
“…Whilst it has been shown previously that neural changes, such as alterations in motor unit properties, can precede the loss of maximal torque production with aging, especially in pre-sarcopenic older adults (36,76,92), the present Whilst older adults demonstrated reduced corticospinal and spinal responses concurrent with increased torque variability compared with young adults, no association was shown between corticospinal and/or spinal responses and torque variability. A previous study demonstrated a lack of relationship between motor performance variability and intracortical inhibitory activity (89), and the present study extends this observation by suggesting a reduction in corticospinal and spinal responses in older age are not related to reductions in motor performance variability during submaximal shortening and lengthening contractions. As previously outlined, there is a possibility that a lack of relation between corticospinal responsiveness and torque variability is due to improvements in motor performance after sufficient familiarisation and repeated performance of the task throughout the experiments (89) despite no observation of a systematic improvement in task performance in both experimental sessions.…”
Section: Relationship Between Functional and Corticospinal Changes Wisupporting
confidence: 87%
See 1 more Smart Citation
“…Whilst it has been shown previously that neural changes, such as alterations in motor unit properties, can precede the loss of maximal torque production with aging, especially in pre-sarcopenic older adults (36,76,92), the present Whilst older adults demonstrated reduced corticospinal and spinal responses concurrent with increased torque variability compared with young adults, no association was shown between corticospinal and/or spinal responses and torque variability. A previous study demonstrated a lack of relationship between motor performance variability and intracortical inhibitory activity (89), and the present study extends this observation by suggesting a reduction in corticospinal and spinal responses in older age are not related to reductions in motor performance variability during submaximal shortening and lengthening contractions. As previously outlined, there is a possibility that a lack of relation between corticospinal responsiveness and torque variability is due to improvements in motor performance after sufficient familiarisation and repeated performance of the task throughout the experiments (89) despite no observation of a systematic improvement in task performance in both experimental sessions.…”
Section: Relationship Between Functional and Corticospinal Changes Wisupporting
confidence: 87%
“…The lack of relationship between maximal strength and torque variability during submaximal contractions has previously been demonstrated in older adults (10), as well as greater torque variability during dynamic contractions (63) and the tendency to overshoot the target torque (48). This greater variability and reduced accuracy in matching the target torque is likely responsible for higher background EMG activity in older adults, a finding consistent with previous literature, especially during fine motor tasks (56,89). Alternatively, the greater agonist EMG activity could stem from differences in antagonist EMG activity.…”
Section: Maximal Torque Production and Torque Variabilitysupporting
confidence: 86%
“…Furthermore, the difference to the results of Berghuis et al. () might simply be explained by the observation that in the majority of studies included in this review, SICI had been tested at rest rather than during activity even though inhibition is well known to be modulated in a task‐dependent manner (Opie & Semmler, ; Papegaaij et al., ; Sidhu et al., ; Soto et al., ). In the present study, however, there was no change in SICI when assessed during rest but only when tested during the previously trained ballistic plantar flexions.…”
Section: Discussionmentioning
confidence: 71%
“…From a functional perspective, however, it makes sense that cortical inhibition is reduced after explosive training in order to ensure high levels of cortical excitatory drive (Kidgell, Bonanno, Frazer, Howatson, & Pearce, 2017). Furthermore, the difference to the results of Berghuis et al (2017) might simply be explained by the observation that in the majority of studies included in this review, SICI had been tested at rest rather than during activity even though inhibition is well known to be modulated in a task-dependent manner (Opie & Semmler, 2016;Papegaaij et al, 2016;Sidhu et al, 2013;Soto et al, 2006). In the present study, however, there was no change in SICI when assessed during rest but only when tested during the previously trained ballistic plantar flexions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation